Validation of the Farsi version of the medical outcomes study-social support survey for mammography - Maryam Khazaee-Pool; Mitra Bahrami; John S. Luque; Tahereh Pashaei; Parvaneh Taymoori; Deam Roshani (BMC, 2018)
Abstract Background Social support can provide psychosocial benefits to promote positive health behaviors such as mammography screening. The purpose of this study was to assess the psychometric properties of the Mammography Social Support (MSS) scale among Iranian woman. Methods Participants were selected from women referring to healthcare centers in Sanandaj, Iran. A total of 434 questionnaires were completed (response rate 91%). The study sample for study 1 included 204 participants for the Exploratory Factor Analysis (EFA). Construct validity was determined by confirmatory factor analysis (CFA) using a study sample of 230 women in study 2. The reliability coefficient for each scale was calculated using Cronbach's alpha, corrected item-total correlations and test-retest respectively. Results CFA affirmed the three-factor structure of the MSS in measuring the functional dimensions of social support for mammography behavior consisting of 19 items. Initial results of the CFA did not fully support the proposed three-factor model. After the model was modified, the fit indices indicated, x 2 was 2.3, Comparative Fit Index (CFI) = 0.96, Tucker- Lewis Index (TLI) = 0.95 providing a strong fit to the data. Cronbach's alphas for the subscales ranged from 0.82 and 0.90, whereas the alpha for the overall scale was 0.91. The 2-week test-retest reliability of MSS was 0.95. Conclusion This study provides evidence for the psychometric properties to support the Farsi version of the MSS when applied to Iranian women. Exploring the three-factor model in relation to related concepts is suggested for future studies.